Effectiveness of Video-Based Education in Improving Adolescent Girls’ Knowledge of Anemia: Efektivitas Edukasi Berbasis Video dalam Meningkatkan Pengetahuan Remaja Putri tentang Anemia - Elisa Goretti Sinaga; Nursyahid Siregar; Nur Aminah (Napande: Jurnal Bidan, 2026)
Background: Anemia is a common health problem among adolescent girls and has an impact on concentration, academic performance, and quality of life. Limited knowledge about the causes, symptoms, and prevention of anemia highlights the importance of health education. This study aims to determine the effect of health education using video media on improving adolescent girls’ knowledge about anemia. Methods: This pre-experimental study with a one-group pretest-posttest design involved 64 eleventh-grade students of SMA Negeri 16 Samarinda selected through random sampling. The intervention consisted of a 5-minute educational video shown three times in one week. Knowledge data were collected using a 20-item multiple-choice questionnaire and analyzed with the Wilcoxon Signed Rank Test, as the Shapiro-Wilk test indicated that the data were not normally distributed. Results: The average knowledge score increased from 41.6 ± 8.6 to 86.6 ± 5.9, with p = 0.000 (p < 0.05), indicating a significant effect. Conclusion: Educational videos are effective in improving adolescent girls’ knowledge about anemia and serve as a practical tool for strengthening school-based health promotion efforts.